The Speech Acts Used among the Eleventh Grade Students of "Usaha Perjalanan Usaha" (UPW) at SMK Negeri 5 Denpasar - ., I GEDE SANDYANA; ., Prof. Dr. Dewa Komang Tantra, M.Sc., Ph.; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA (Jurnal Pendidikan Bahasa Inggris, 2014)
This study was focused at finding out 1) the speech acts used, 2) the styles of politeness used, and 3) the speaking errors made by the students in handling ticket reservation. It was a qualitative research, and the subjects of the study were the eleventh grade students of UPW in SMKN 5 in academic year 2013/2014. The research data were collected through simulated speech. The speech acts that were used the most by the students were expressive. There were 37% expressive, followed by Assertive 34%, directive 18%, and commisive 11%. The politeness styles showed that 91% speech acts were categorized as polite and there were 9% speech acts categorized as impolite. The maxims that the students used were tact, generosity, approbation, and modesty. The students made some errors in speaking, grammar 25%, content 21%, pronunciation 20% and diction 6%. It can be concluded that the speech acts, politeness, and speaking skills have a significant rule to help the students to be able to communicate well. English teachers should teach the students more expressions to express actions and also let the students know about politeness so that they can be good and polite in communication.keyword : Speech acts, politeness, speaking errors